1997
DOI: 10.1021/js960408n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Skin Metabolism on Percutaneous Penetration of Lipophilic Drugs

Abstract: Effects of skin metabolism on percutaneous penetration of drugs with high lipophilicity were studied in vitro using rat skin pretreated with and without an esterase inhibitor, diisopropyl phosphorofluoridate [also known as diisopropyl fluorophosphate (DFP)]. Without DFP, about 96% of the total penetrated amount appeared as metabolized p-hydroxybenzoic acid in the receptor fluid after application of butylparaben, whereas about 30% penetrated as intact form after application of propylparaben. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 13 publications
2
51
0
3
Order By: Relevance
“…In fact, increased plasma levels of E 1 and estrogen overloading the liver changing protein synthesis due to oral E 2 replacement have been suspected to be a reason for adverse effects [10,14]. Besides influencing the E 2 /E 1 ratio in plasma, cutaneous E 2 metabolism may also influence permeation/penetration of the native entity, since metabolites with different physicochemical properties distribute independently from native drug [24].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, increased plasma levels of E 1 and estrogen overloading the liver changing protein synthesis due to oral E 2 replacement have been suspected to be a reason for adverse effects [10,14]. Besides influencing the E 2 /E 1 ratio in plasma, cutaneous E 2 metabolism may also influence permeation/penetration of the native entity, since metabolites with different physicochemical properties distribute independently from native drug [24].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the EC ScientiÂźc Panel on Food Additives, Flavourings, Processing Aids and Materials in Contact with Food of the European Food Safety Authority (EFSA) reviewed propylparaben (EFSA, 2004) and was unable to establish a no-observed-adverse-effect-level for reproductive and endocrine toxicity, and consequently an ADI, effectively recommending its exclusion/withdrawal from food use. These regulatory evaluations involve oral exposures but it has been previously suggested that dermal application of paraben esters may represent a special case because of a higher probability of escaping limited skin esterase action (Bando et al, 1997;Oh et al, 2002;Prusakiewicz et al, 2006;El Hussein et al, 2007;Harville et al, 2007;Janjua et al, 2007) and local subcutaneous tissue accumulation (see Harvey and Darbre, 2004), indicating a need for regulatory risk assessment harmonization. Harmonization would require withdrawal of butylparaben and propylparaben from cosmetics.…”
Section: Regulatory Status Of Parabensmentioning
confidence: 99%
“…Parabens are known to be readily absorbed through the skin and it has been suggested that hydrolysis of parabens by skin esterases could be incomplete in the context of increasing cosmetic useage and inter-individual variations (Darbre et al, 2004a;Harvey and Darbre, 2004). In vitro studies have shown that 30% of applied propylparaben penetrates the skin intact in rat skin (Bando et al, 1997), and after 8 h contact, penetration of some esters can be even higher with up to 60% of methylparaben and 40% of ethylparaben crossing rabbit skin intact (Pedersen et al, 2007). In humans, variations between individuals in hydrolysis of parabens have now been shown in the case of human liver esterases (Jewell et al, 2007), although studies are still lacking for skin esterases.…”
Section: Introductionmentioning
confidence: 99%
“…Parabens applied to skin are known to be partly metabolised by four carboxyl esterases capable of hydrolysing the different parabens to phydroxybenzoic acid (Lobemeier et al 1996). However, in vitro studies on penetration of rat skin by butylparaben and propylparaben indicated that 4% of butylparaben and 30% of propylparaben were not hydrolysed (Bando et al 1997). In view of the oestrogenic properties documented by Routledge et al (1998) and the present work, more data are clearly needed on the systemic exposure of humans to this group of preservatives.…”
Section: Resultsmentioning
confidence: 68%